Training on the use of Light Fire Extinguisher for Residents in densely populated housing Duri Pulo Subdistrict, Central Jakarta - Pauhesti Pauhesti; Sri Feni Maulindani; Kartika Fajarwati Hartono; Riskaviana Kurniawati; Lailatul Wastiyah; Theresia Dolfina Kilmas; Ni Wayan Nanik Juliantari; Ade Kurniawan Saputra (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The dense population in a residential area often faces a high risk of fire. The main factor, apart from the dense population, is also due to limited access to fire extinguishers and vulnerable environmental conditions. A simple and effective solution to handle small fires before they spread widely is to use APAR (light fire extinguishers). This Community Engagement (Community service) activity aims to increase awareness and skills among residents in the use of APAR, so that they can better prepare for potential fires. This Community service was carried out in a densely populated area in the Duri Pulo sub-district, Central Jakarta. The Community service method was carried out through counseling and direct training on how to use APAR. At the end of this activity, 10 APAR units were handed over from the COMMUNITY SERVICE FTKE Trisakti University Team to Karang Taruna DuriPulo to be distributed and installed in strategic locations within the area.